2016
DOI: 10.1186/s13098-015-0122-4
|View full text |Cite
|
Sign up to set email alerts
|

Juçara pulp supplementation improves glucose tolerance in mice

Abstract: BackgroundThe consumption of hyperlipidic and hypercaloric diet is considered a major factor to promote obesity and the consumption of food with antioxidant properties, like Juçara (Euterpe edulis Mart), could be a tool to prevent the deleterious effect of high white adipose deposition. The aim of the present study was to evaluate the effect of administration of juçara pulp in mice fed a high-fat, high-calorie diet on glucose tolerance and adipose tissue inflammatory status.MethodsMice were distributed into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 29 publications
1
39
1
Order By: Relevance
“…The elevation of these inflammatory adipokines may contribute to the development of insulin resistance and metabolic syndrome [25]. Although results showed no significant difference in inflammatory cytokines between the control and hypercaloric groups of the present study, the hypercaloric diet given to the H group had been able to promote inflammation of adipose tissue in a previous study by our research group [14]. The study conducted by Cano et al in 2009 [26] may explain this unexpected result of our study, since authors had verified that a high-fat diet is able to disrupt the daily patterns of the cytokines adiponectin, IL-6 and TNF-a.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…The elevation of these inflammatory adipokines may contribute to the development of insulin resistance and metabolic syndrome [25]. Although results showed no significant difference in inflammatory cytokines between the control and hypercaloric groups of the present study, the hypercaloric diet given to the H group had been able to promote inflammation of adipose tissue in a previous study by our research group [14]. The study conducted by Cano et al in 2009 [26] may explain this unexpected result of our study, since authors had verified that a high-fat diet is able to disrupt the daily patterns of the cytokines adiponectin, IL-6 and TNF-a.…”
Section: Discussioncontrasting
confidence: 57%
“…Although the removal of tissue samples from the mice in the present study had been performed concurrently with the study by Oyama et al in 2016 , it is possible that we performed the removal at a time when no statistical difference could have been observed between the groups that received the control and high‐fat diets, which may have been due to hormonal alteration of the circadian cycle caused by the high‐fat diet. Therefore, we cannot infer that the chia caused anti‐inflammatory action in the epididymal adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in our group showed that jussara supplementation during pregnancy and lactation modulates gene and protein expression of inflammation biomarkers and improves colonic expression of ZO-1 in offspring (Morais et al, 2016(Morais et al, , 2014. Additionally, jussara supplementation improves glucose tolerance in mice (Oyama et al, 2016). The high concentration of phenolic compounds, especially anthocyanins, appears to be responsible for these biological effects.…”
Section: Introductionmentioning
confidence: 99%
“…Jussara has been extensively considered as a superfruit and highlights the potentialities related to the Brazilian biodiversity as a source of high-value products. Studies in our group showed that jussara, besides the colorant power provided by the anthocyanins, is accounted for in several beneficial results from a perspective of health and well-being [27,[30][31][32]. Jussara pulp has been recognized as a superfood due to its composition, mainly, for the high concentration of anthocyanins and other phenolic compounds; in fact, these bioactive compounds are considered an attractive source of pigments and also means to ward off several diseases [27,33,34].…”
Section: Introductionmentioning
confidence: 99%